Land Use Pattern in Azamgarh District (UP): A Geographical Analysis - Kumar, Narender; Tiwari, Seema (National Geographical Journal of India, 2022)
The agricultural land use refers to primary use of geographical area for different purposes and activities. Land use is the surface utilization of all developed and vacant land on a specific point at given time and space (Mandal, 1982). It is a very important indicator of agricultural development. The land use analysis is an important aspect of geographical studies which provides proper guidelines for regional planning and development and also for future orientation of agriculture. Therefore, the study of land use and its change has been carried out by many researchers and geographers at national and international level. The study reveals that marginal changes have occurred in all land use categories except for the proportion of area under forests which has very low increase from 0.02% in 1995 to 0.03% in 2014. Net sown area to total area has slightly declined from 72.81% in 1995 to 71.81% in 2014, while area under non-agricultural uses has negative change which decreased from 16 % in 1995 to 9.19 % in 2014. The main objective of the study is to find out spatio-temporal change of land use pattern in Azamgarh district. The present study is based on secondary data. This data has been collected from District Agriculture Office and District Statistical Magazine for the year 1995 to 2014. After analyzing the data different relevant diagrams and maps are prepared.